Avaliação da bioatividade de extratos de Araucaria angustifolia (Bertol.) Kuntze - Oliveira, Anielle de (2019)
Diabetes Mellitus is a chronic metabolic disease, which can lead to high blood glucose levels, one of the alternatives to minimize effects related to hyperglycemia is the inhibition of carbohydrate hydrolyzing enzymes. In addition, another disease that has caused great concern is Alzheimer’s, in which one of its hypotheses is that it involves the functioning of cholinergic system. Araucaria angustifolia (Bertol.) Kuntze is a conifer belonging to the Araucariaceae family, grown mainly in southern Brazil, some studies have shown the phenolic compounds in the pine shells and seeds, which may act as antioxidants agents. Therefore, the objective of this work was to characterize the residues extracts (CW and PS) from pinhão consumption and to evaluate its bioactivity. The effects of the extracts presence on the activity of human salivary and porcine pancreatic amylases by in vitro and in vivo tests and also acetylcholinesterase and butyrylcholinesterase. CI50 results used for alpha amylase were 740 and 129 µg.mL-1 and for porcine pancreatic 1871.66 and 460.70 µg.mL-1 for extracts CW and PS respectively, while for acetylcholinesterase were 7.31 µg.mL-1 for WC and 8.09 µg.mL- 1 for PS and butyrylcholinesterase assays were 1.94 µg.mL-1 and 6.96 µg.mL-1 for WC and PS, also PS presented cytotoxic activity to tumor cells. These data showed that both extracts acted as enzyme inhibitors and could contribute to the treatment of diseases such as diabetes and Alzheimer’s.